Penerapan al-Qawā‘id al-Fiqhiyyah al-Iqtishādiyyah dalam Transaksi Saham Syariah: Analisis Kaidah al-Ghunm bi al-Ghurm di Pasar Modal Indonesia - Budi Purnomo; Hasan Bisri; Ayi Yunus (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The principles of al-Qawā‘id al-Fiqhiyyah al-Iqtishādiyyah serve as a fundamental normative framework for assessing the Sharia compliance of contemporary financial transactions, including Islamic stock trading in the capital market. Among these principles, the rule of al-ghunm bi al-ghurm—which asserts that profit is only legitimate when accompanied by risk—plays a central role in distinguishing Sharia-compliant investment from prohibited speculative practices. This article aims to analyze the challenges and solutions in implementing the al-ghunm bi al-ghurm principle in Islamic stock transactions within the Indonesian Sharia capital market. Employing a qualitative research method based on a literature review, this study examines classical and contemporary fiqh doctrines, DSN-MUI fatwas, and relevant capital market regulations. The findings reveal several key challenges, including low risk literacy among Sharia investors, the emergence of expectations for risk-free returns, speculative trading behavior, and the development of digital investment products that potentially undermine genuine risk-sharing mechanisms. To address these issues, the article proposes strengthening Sharia-based risk education, enhancing risk disclosure and transparency, reaffirming the prohibition of profit guarantees, and improving Sharia screening mechanisms for listed companies. This study underscores the importance of al-ghunm bi al-ghurm as both a normative and practical foundation for fostering a fair, resilient, and sustainable Sharia capital market in Indonesia.